Electrically Small Sleeve Baluns Constructed Using Additive Manufacturing - David S. Mitchell; Jessica E. Ruyle (IEEE Access)
This paper documents a novel method for the design and construction of unfolded, folded, and dielectrically-loaded sleeve baluns using additive manufacturing to achieve an electrically small form factor for size and weight constrained applications. Single and double-folded sleeve baluns were constructed, tested, and compared to standard sleeve baluns. The baluns decreased 40% in size with each successive folding, with the smallest air-core baluns being 36% the size of a standard sleeve balun. Dielectric-loading was utilized to further miniaturize, resulting in a balun that is only 21% the size of a standard sleeve balun. The double-folded balun constructed using additive manufacturing is also only 40% of the weight of a standard sleeve balun. The Common Mode Rejection Ratio (CMRR) was above 38 dB for all baluns. These baluns achieve a small form factor, similar to ferrite beads, making them usable as inline components in systems where traditional sleeve baluns are too large and heavy.